PEMAHAMAM DAN IMPLEMENTASI NILAI- NILAI PANCASILA DALAM KEHIDUPAN SEHARI-HARI BAGI BANGSA INDONESIA: MURLINUS - Murlinus (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
Pancasila values must be known, understood, and implemented by the nation of Indonesia in daily life to be able to realize the goal of realizing the proclamation of independence. However, in the present knowledge, understanding of the next generation of the nation against the values that are contained in the Pancasila, the more degraded and eroded by the battle of the new values that are not in accordance with the nation's identity. The problem of understanding resulted in the start of abandoned and forgotten Pancasila. Therefore, the implementation required values of Pancasila in order to be referable to the people of Indonesia in answering the various question facing current and future, both issues that come from within and from outside. before the success of the implementation we do the values of Pancasila, Pancasila, alienation from the real life of the nation of Indonesia..